2010
DOI: 10.1093/jac/dkq388
|View full text |Cite
|
Sign up to set email alerts
|

Trends in production of extended-spectrum  -lactamases among Enterobacteriaceae of clinical interest: results of a nationwide survey in Belgian hospitals

Abstract: the rapid emergence of multiresistant CTX-M-15-producing E. coli isolates is of major concern and highlights the need for further surveillance in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 39 publications
4
38
0
1
Order By: Relevance
“…Although the prevalence of ertapenem nonsusceptibility in the Enterobacteriaceae family is relatively lower than that in Pseudomonas aeruginosa and Acinetobacter baumannii, the current trend of rising ertapenem resistance of the Enterobacteriaceae has become a great concern (13,19,27). Surveillance of antimicrobial susceptibility by the Study for Monitoring Antimicrobial Resistance Trends (SMART) reported that the rate of susceptibility of E. cloacae strains to ertapenem decreased from 100% (2002) to 89.7% (2009) in China (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of ertapenem nonsusceptibility in the Enterobacteriaceae family is relatively lower than that in Pseudomonas aeruginosa and Acinetobacter baumannii, the current trend of rising ertapenem resistance of the Enterobacteriaceae has become a great concern (13,19,27). Surveillance of antimicrobial susceptibility by the Study for Monitoring Antimicrobial Resistance Trends (SMART) reported that the rate of susceptibility of E. cloacae strains to ertapenem decreased from 100% (2002) to 89.7% (2009) in China (27).…”
Section: Discussionmentioning
confidence: 99%
“…First, despite the extended use of AMC and TZP in areas in which CTX-M enzymes are prevalent (14,18,53), IR-CTX-Ms have never been described in clinical isolates (6). Second, several widespread CTX-Ms, such as CTX-M-15, are frequently coselected in the same bacterial host with other ␤-lactamases, as those of the OXA type (10,60), conferring variable degrees of resistance to BBLIs (32).…”
Section: Discussionmentioning
confidence: 99%
“…The present epidemiological situation has forced a reexamination of the therapeutic possibilities of BBLIs, some of which suggest a positive effect both in severe and in uncomplicated infections (50,56). The current resistance rates to BBLIs in Europe account for 12% and 25% of ESBL-producing Escherichia coli and Klebsiella strains, respectively (12,53). In a number of CTX-M-producing Enterobacteriaceae, as frequently happens for CTX-M-15 producers, BBLI resistance is associated with the coproduction of OXA-1 ␤-lactamase (10) or porin loss (59), whereas no natural CTX-M enzyme has been found to confer resistance to BBLIs (6).…”
mentioning
confidence: 99%
“…All the carbapenemases encountered during this study were correctly detected by the BC-GN assay. Along with the detection of carbapenemase, the BC-GN assay also detects the presence of the CTX-M type, which is rapidly spreading among Enterobacteriaceae worldwide, replacing the TEM and SHV types as the predominant ESBLs in many countries (10,11). Out of the nine ESBLs detected by the phenotypic method, all but one were the CTX-M type.…”
mentioning
confidence: 99%